A COMPARATIVE ANALYSIS OF THE BASIC METHODS OF DIGITAL SIMULATION OF ANALOG SYSTEM - Bezrukov, V. V.; Honcharov, K. V.; Ivakhnenko, D. F. (Science and Transport Progress, 2006)
Basic methods of digital design of the analog system – that of digitization of differential equation, of digitization of impulsive description and a bilinear one – have been considered. On the example of an oscillating link, as an analog prototype, errors of frequency-time of digital design descriptions have been calculated. Conclusions in relation to exactness of digital design by different methods have been drawn.